Single-step bioconversion of starch to bioethanol by the coculture of ragi tapai and saccharomyces cerevisiae - Azmi, Azlin Suhaida; Hasan, Masitah; Mel, Maizirwan; Ngoh, Cheng (The Italian Association of Chemical Engineering, 2009)
The objective of this preliminary experiment was to test the hypothesis that coculturing commercialised ragi tapai with S. cerevisiae might have improved the ethanol production and reduce the accumulation of inhibitory concentration of reducing sugar and this would enhance the amylolytic activity. Co culture of a commercialised ragi tapai with S cerevisiae using unhydrolysed raw starch in single step-fermentation produced a high ethanol concentration. A 35.26 giL of ethanol was produced when the starch was inoculated with ragi tapai and cocultured it with Scerevisiae 1 h later. This was 48% higher than the yield obtained when the starch was inoculated with ragi tapai only (23.79 giL). The glucose concentration was maintained at low concentration in the coculture medium compared to the medium with ragi tapai only. However, stachyose concentration profile was higher in cocultured medium as compared to the one with ragi tapai only. In conclusion, coculture ragi tapai with S cerevisiae enhanced the ethanol production and prevented the inhibitory effect of reducing sugars on amylase activity.